2009
DOI: 10.1158/1535-7163.mct-09-0045
|View full text |Cite
|
Sign up to set email alerts
|

Folate-mediated intracellular drug delivery increases the anticancer efficacy of nanoparticulate formulation of arsenic trioxide

Abstract: Arsenic trioxide (As2O3) is a frontline drug for treatment of acute promyelocytic leukemia and is in clinical trials for treatment of other malignancies, including multiple myeloma; however, efforts to expand clinical utility to solid tumors have been limited by toxicity. Nanoparticulate forms of As2O3 encapsulated in 100-nm-scale, folate-targeted liposomes have been developed to lower systematic toxicity and provide a platform for targeting this agent. The resultant arsenic “nanobins” are stable under physiol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
118
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(125 citation statements)
references
References 38 publications
(54 reference statements)
4
118
0
Order By: Relevance
“…The human ovarian carcinoma SKOV3 is a widely used folate receptor positive cell line, however for human breast carcinoma MCF-7 cell line, different literature reports quite contradictory folate receptor expression levels. Jie et al employed MCF-7 as a folate receptor overexpressed cell line [31] while Haimei et al used MCF-7 as a negative control [32]. In this study, we tested the folate receptor expression level of the MCF-7 and SKOV3 cell lines.…”
Section: Folate Receptor Expressionmentioning
confidence: 99%
“…The human ovarian carcinoma SKOV3 is a widely used folate receptor positive cell line, however for human breast carcinoma MCF-7 cell line, different literature reports quite contradictory folate receptor expression levels. Jie et al employed MCF-7 as a folate receptor overexpressed cell line [31] while Haimei et al used MCF-7 as a negative control [32]. In this study, we tested the folate receptor expression level of the MCF-7 and SKOV3 cell lines.…”
Section: Folate Receptor Expressionmentioning
confidence: 99%
“…It has been shown that uptake of folate-targeted drug delivery systems is decreased in tumoral models which have lower density of folate receptors, such as HeLa and MCF-7 cells. 37 Thus, the spectra of uses of those molecules are restricted depending on the cell model studied. On the other hand, the role of ascorbic acid in cancer metabolism is well described for several tumoral lineages and its high uptake is a characteristic common to most solid or nonsolid tumors analyzed, [38][39][40] which makes it an interesting molecule to target a broader spectra of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Li and Huang showed that targeted liposomes are able to localize to and effectively deliver siRNA to tumors in a xenograft model of human lung cancer [37]. Folate-targeted liposomes encapsulating arsenic trioxide, a toxic chemical with a low therapeutic index that has been used in the treatment of some forms of leukemia, was recently shown to be effective against malignant cells that express the folate receptor [38].…”
Section: Ligand-targeted Liposomesmentioning
confidence: 99%